Scoring Analysis of the 2015 World Wrestling Championships. Issue 1 (2nd January 2016) - Tünnemann, Harold
ABSTRACT: The videos of all matches from the 2015 Senior World Championships were analyzed for scoring and technique. The world championship in a pre-Olympic year, is also the first opportunity for the athletes to qualify the weight class (attained by finishing in the top 6) for their country for the Olympic Games. Countries and qualified weight classes are presented. Attack efficacy, represented by points scored per minute, is presented for the style as a whole, for the top countries and for the weight class champions. The technical structure of the champions, with scoring by type of technique, is also presented. This was done for all three styles-Men's Freestyle, Women's Freestyle and Greco-Roman. All three styles moved in a positive direction in regard to increased activity and scoring as a result of the most recent rules changes. However, Greco-Roman must explore ways to make larger strides in the variety of scoring, especially techniques from the standing position.